2014
DOI: 10.1097/aln.0000000000000148
|View full text |Cite|
|
Sign up to set email alerts
|

Preclinical Toxicity Screening of Intrathecal Oxytocin in Rats and Dogs

Abstract: Background Anatomic, physiologic, and behavioral studies in animals suggest that spinally released oxytocin should produce analgesia in humans and may also protect from chronic pain after injury. Here we report preclinical toxicity screening of oxytocin for intrathecal delivery. Methods Intrathecal oxytocin, 11 μg (6 IU) or vehicle, was injected intrathecally in 24 rats, followed by frequent behavioral assessment and histologic examination of spinal contents 2 or 14 days after injection. In 3 dogs, a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The significant increase in brain homogenate serotonin level in OXT subgroup (A) of the present study is in agreement with previous animal studies which suggested that serotonergic and oxytocinergic neurotransmission interact anatomically and functionally (Scantamburlo et al, 2009;Montag et al, 2011;Silva et al, 2013). Yaksh et al (2014) found that rats treated with oxytocin have an increased synthesis of 5-HT in the frontal cortex and brain stem. In addition, brain homogenate dopamine level was significantly increased which coincided with the study of Baskerville and Douglas (2010) who reported increase dopamine release in the ventral striatum and nucleus accumbens after oxytocin infusion in ventrotegmental dopaminergic neurons.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The significant increase in brain homogenate serotonin level in OXT subgroup (A) of the present study is in agreement with previous animal studies which suggested that serotonergic and oxytocinergic neurotransmission interact anatomically and functionally (Scantamburlo et al, 2009;Montag et al, 2011;Silva et al, 2013). Yaksh et al (2014) found that rats treated with oxytocin have an increased synthesis of 5-HT in the frontal cortex and brain stem. In addition, brain homogenate dopamine level was significantly increased which coincided with the study of Baskerville and Douglas (2010) who reported increase dopamine release in the ventral striatum and nucleus accumbens after oxytocin infusion in ventrotegmental dopaminergic neurons.…”
Section: Discussionsupporting
confidence: 82%
“…This excludes the cardiovascular complications, which goes in line with the previous study of Yang et al (2011b). However ABP and HR were significantly decreased after intravenous OXT administration and this coincided with the previous study of Yang et al( 2014) which demonstrated that intravenous OXT promoted a direct negative inotropic and chronotropic effects in rats (Yaksh et al, 2014). OXT acts on specific oxytocin atrial cardiomyocytic receptors, stimulate the release of acetylcholine, decreasing the rate and force of cardiac contraction (Montag et al, 2011) and, stimulates the release of atrial natriuretic peptide (ANP) which causes bradycardia, naturesis and hypotension (Ahmed et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Besides, intraperitoneal administration of synthetic OT causes a 40-fold increase in plasma OT levels (here >1500 pmol/L) in mice (Neumann et al, 2013). A preclinical toxicity screen suggests that plasma OT concentrations could be increased by 500 times from a baseline of approximately 100 to 50,000 pmol/L after intrathecal injections of OT (550 lg) without neurotoxicity in dogs (Yaksh et al, 2014). If plasma OT concentrations are increased by 500 times in rats, it will be close to the working concentration (10 À7 M) of OT in this study.…”
Section: Discussionmentioning
confidence: 97%
“…12 Scratching behavior in rodents following intrathecal oxytocin is directed to the dermatomes near the injection site, consistent with a pruritic effect or, potentially hypesthesia. 14 This does not occur in dogs 13 and no subject in the current study reported itching or hypesthesia, so it is likely that there is a species dependent effect with rodents being susceptible.…”
Section: Discussionmentioning
confidence: 91%